Implementasi Pengelolahan Sampah Rumah Tangga berbasis Project Based Learning melalui Pemberdayaan Masyarakat Dusun Panjen - Fauzi, Achmad; Damayanti, Fransiska Erna; Budi, Yulifah Salistia (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2024)
Waste this a symptom for the world that must be handled properly and correctly and in an integrated manner. The increasing population can contribute to the high volume of waste, especially since the most waste is organic waste, where this waste can be used disposed of. Meaning of activity analyze household waste utilization model project-based learning through community empowerment in Panjen Hamlet. The method used is direct counseling and training for PKK-KB mothers including herbal liquid, visionary, larvae. The qualitative research design collects data using interviews with 7 participants. Activity device is the implementer himself. Analysis used Colaizzi method. Results the study obtained 4 themes, namely: 1) Positive response to the results of socialization and training, 2) Organic & Inorganic Waste Management project understanding model, 3) Hopes after utilization of household waste training, 4) Sustainability of household waste management programs. Overview of the activities of utilization management based on Based Learning is an example for residents, especially mothers from the Panjen Hamlet, Jambewangi Village KB fosters a sense of happiness fostering a sense of love for the surrounding environment so that they are willing to utilize and manage household waste in Panjen Hamlet.